Pengembangan Model Pembelajaran Dengan Multimedia Dalam Pembelajaran Pencak Silat di Masa Pandemi Pada Siswa - Arief Nur Wahyudi; Abi Zahed Al Qurtubi; aba sandy prayoga (ILIN Institute Makassar, 2021)
This study aims to see the level of student learning during the Covid-19 pandemic with the background of the Covid-19 epidemic where the teaching and learning process is carried out courageously. This study aims to produce a multimedia development product for learning pencak silat, Physical Education, Sports and Health for fourth grade elementary school students. This research used a qualitative method, the data source of this research was the students of class IV SDN Wonokerto IV in the academic year 2020/2021 which were planned as many as 5 students. The data technique uses the method of observation and questionnaires to material experts, media experts and students. The results of the material expert validation were